Efeito miragem resolvido no tempo : teoria e experimentos - Bernabé, Hilton Souza (2012)
A time-resolved three-dimensional model for photothermal beam deflection is presented for the measurement of thermal properties of opaque materials. We derive the analytical solutions for the laser induced temperature profiles in the sample and in the fluid around the sample assuming flux discontinuity at the interface sample/fluid. We compare the analytical solutions with all numerical modeling using finite element analysis. The photothermal deflection signal is calculated and an expression is provided for the normal photothermal signal at the photodetector position. We use the model and the experimental method to investigate opaque plastic and metals, and the results for the thermal properties of the samples are in excellent agreement with the literature values.